2021
DOI: 10.1108/jmhtep-08-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian cultural beliefs about mental health conditions and traditional healing: a qualitative study

Abstract: Purpose This study aims to explore how cultural beliefs and traditions are integral to understanding indigenous mental health conditions (MHCs) and traditional healing (TH). However, Nigerian cultural beliefs about MHCs and TH are under-researched. Design/methodology/approach This study adopted a qualitative design using critical realist and social constructionist perspectives to explore Nigerian mental health-care practitioners (MHCPs) and lay participants’ (LPs) views regarding MHCs and TH. Purposive and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…Data collection involved dialogues with each of the 19-participating healers (Table 1). Dialogues, as opposed to interviews, are the preferred data gathering strategy when engaging in research with elders in the African culture more especially when studying indigenous knowledge systems (Denzin et al, 2008), as underpinned by Afrocentric theoretical features (Jidong et al, 2021b;Asante, 2007). Data was also collected through observations including participating in field trips to the forest to harvest medicinal plants.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection involved dialogues with each of the 19-participating healers (Table 1). Dialogues, as opposed to interviews, are the preferred data gathering strategy when engaging in research with elders in the African culture more especially when studying indigenous knowledge systems (Denzin et al, 2008), as underpinned by Afrocentric theoretical features (Jidong et al, 2021b;Asante, 2007). Data was also collected through observations including participating in field trips to the forest to harvest medicinal plants.…”
Section: Instrumentsmentioning
confidence: 99%
“…Despite the growing support for the use of herbal medicines for mental problems, it continues to be ridiculed and under-supported in mainstream mental health-care systems (Burns and Tomita, 2015; Nwobodo and Offiah, 2017). Even so, those who rely on the herbs believe they are fairly safe, efficacious, readily available and have no adverse side effects (Nwobodo and Offiah, 2017; Jidong et al , 2021b). Further support comes from scholars who have pointed out that traditional ethnobotanicals’ safety and efficacy is demonstrated by their long history of use in various parts of the world (Bouso and Sanchez-Aviles, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study assessing public beliefs and attitudes towards BDs disorders in a UK sample, BDs were believed to have both biomedical and psychosocial origins; however, they were associated with positive stereotypes such as the belief that individuals with BDs are intelligent and creative (Ellison et al,2014). Discrimination against mental illness in Africa has often been documented in published literature (Jidong et al, 2021a). Such discriminatory acts among the general population sometimes arise from misinformation about mental disorders (Jidong et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, some studies have explored lived experiences of maternal anxiety and depression (e.g., Jidong et al, 2021c); however, there is a dearth of literature investigating how the general public views individuals with BDs. A previous study of rst-degree relatives of patients with schizophrenia and major affective disorders with psychotic symptoms in psychiatric hospitals in Nigeria found that contrary to relatives of sickle cell patients who mostly cited genetic components as the root cause of the patients' illness, caregivers of patients with psychotic illnesses had more religious-in uenced opinions about the aetiology of these illnesses (Oheari and Fido, 2001;Jidong et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation